2020
DOI: 10.1186/s12887-020-02063-3
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of adverse childhood experiences (ACEs) among a community-based sample of parents and adolescents

Abstract: Background: Despite increased understanding of Adverse Childhood Experiences (ACEs), very little advancement has been made in how ACEs are defined and conceptualized. The current objectives were to determine: 1) how well a theoretically-derived ACEs model fit the data, and 2) the association of all ACEs and the ACEs factors with poor self-rated mental and physical health. Methods: Data were obtained from the Well-Being and Experiences Study, survey data of adolescents aged 14 to 17 years (n = 1002) and their p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 58 publications
3
39
0
2
Order By: Relevance
“…Table 4 shows the distribution of mental health outcomes for ACEs reported prospectively and retrospectively, categorized as ‘less than four’ or ‘four or more’. Given patterns in the literature associating adversity in childhood with poor mental health [ 12 , 13 ], it is expected that a greater proportion of respondents who report four or more ACEs will present with psychological distress. Using prospective reports of ACEs there appears to be little significance between reported ACEs and psychological distress (somatization, p = 0·465; anxiety, p = 0·263; social dysfunction, p = 0·522; depression, p = 0·050; GHQ total, p = 0·273).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 shows the distribution of mental health outcomes for ACEs reported prospectively and retrospectively, categorized as ‘less than four’ or ‘four or more’. Given patterns in the literature associating adversity in childhood with poor mental health [ 12 , 13 ], it is expected that a greater proportion of respondents who report four or more ACEs will present with psychological distress. Using prospective reports of ACEs there appears to be little significance between reported ACEs and psychological distress (somatization, p = 0·465; anxiety, p = 0·263; social dysfunction, p = 0·522; depression, p = 0·050; GHQ total, p = 0·273).…”
Section: Resultsmentioning
confidence: 99%
“…For example, one study linked a cluster of ACEs related to abuse and neglect to higher severity bipolar disorder and schizophrenia, compared to a cluster of social support-related ACEs [12] . In another study on the clustering of individual ACEs, a child maltreatment and peer victimization group was associated with double the odds of self-rated poor physical health and three times the odds of self-rated poor mental health, compared to a household challenges grouping which was linked to an almost 3-fold chance of reporting poor physical health and six-times odds of reporting poor mental health [13] .…”
Section: Introductionmentioning
confidence: 95%
“…Adverse Childhood Experiences (ACEs) ACEs included adolescent experiences of emotional neglect, emotional abuse, exposure to verbal intimate partner violence (IPV), spanking, peer victimization, parental separation or divorce, parental trouble with police, parental gambling, foster care or child protective organization (CPO) contact, household substance use, household mental illness, household poverty, and living in an unsafe neighbourhood. ACEs were selected based on work from a previous study (Afifi, Salmon, et al, 2020a). We could not assess other important ACEs, including physical abuse, sexual abuse, or physical neglect (Felitti et al, 1998), due to requirements of the Health Research Ethics Board related to the Manitoba child welfare mandatory reporting laws.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, child and adolescent mental health programs should consider collecting more information about childhood exposure to adversities. A recent Canadian study has suggested that in addition to the ACE items, expanded ACEs such as household gambling problems, spanking, peer victimization, and neighborhood safety factor well with child maltreatment and household dysfunction and are associated with poor physical and mental health [ 56 ]. Collecting data on these emerging adversities through the health system and using them to predict health outcomes could also be the future direction.…”
Section: Discussionmentioning
confidence: 99%